Search for resonant pair production of Higgs bosons decaying to two bottom quark-antiquark pairs in proton-proton collisions at 8TeV - Khachatryan, V. (2015)
A model-independent search for a narrow resonance produced in proton-proton collisions at root s= 8TeV and decaying to a pair of 125GeV Higgs bosons that in turn each decays into a bottom quark-antiquark pair is performed by the CMS experiment at the LHC. The analyzed data correspond to an integrated luminosity of 17.9fb(-1). No evidence for a signal is observed. Upper limits at a 95% confidence level on the production cross section for such a resonance, in the mass range from 270 to 1100 GeV, are reported. Using these results, a radion with decay constant of 1 TeV and mass from 300 to 1100 GeV, and a Kaluza-Klein graviton with mass from 380 to 830 GeV are excluded at a 95% confidence level. (C) 2015 CERN for the benefit of the CMS Collaboration. Published by Elsevier B.V.